A negative-carbon footprint process with mixed biomass feedstock maximizes conversion efficiency, product value and CO2 mitigation. (May 2022) - Jiang, Peng; Zhao, Guanhan; Liu, Li; Zhang, Hao; Mu, Liwen; Lu, Xiaohua; Zhu, Jiahua
Graphical abstract: Highlights: Co-production of activated carbon and bio-fuel with waste biomass resources. Mixed biomass maximizes process efficiency, product value and CO2 mitigation. TEA and LCA demonstrate short PBP of 3.16 years and low GWP of −2.37 kg CO2 -eq. Abstract: The great variety of biomass species offers unique features for synergistic optimization of process outcomes. In this work, spent mushroom substrate and bagasse with optimize ratio were processed to produce value-added products of activated carbon and biofuel yet achieve negative CO2 emission. By integrating experimental characterization, this work uses process simulation, techno-economic analysis and life-cycle assessment to evaluate the techno-economic viability and CO2 footprint of processes with single or dual-/mixed-biomass feedstocks. The combination of biomass species provides unique match of the production of flue gas and primary carbon that is critical for the optimization of mass and energy flow. Such combination has been demonstrated effective to improve product yield and energy efficiency. Results show that mixed biomass feedstock offers favourable figures such as high carbon efficiency of 66.74%, short payback period of 3.16 years, considerable net present value of 80.48 million dollars, and low GWP of −2.37 kg CO2 -eq.